1999
DOI: 10.1093/emboj/18.9.2411
|View full text |Cite
|
Sign up to set email alerts
|

The importin β/importin 7 heterodimer is a functional nuclear import receptor for histone H1

Abstract: Import of proteins into the nucleus proceeds through nuclear pore complexes and is largely mediated by nuclear transport receptors of the importin beta family that use direct RanGTP-binding to regulate the interaction with their cargoes. We investigated nuclear import of the linker histone H1 and found that two receptors, importin beta (Impbeta) and importin 7 (Imp7, RanBP7), play a critical role in this process. Individually, the two import receptors bind H1 weakly, but binding is strong for the Impbeta/Imp7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
238
1
15

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 238 publications
(269 citation statements)
references
References 73 publications
(136 reference statements)
15
238
1
15
Order By: Relevance
“…As expected, in the presence of retic* nuclear import of L23a was clearly detectable. In conclusion, these data in combination with our previous results (9) suggest that there is only one functional import receptor for histone H1 in eukaryotic cells, namely the Imp␤-Imp7 heterodimer.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…As expected, in the presence of retic* nuclear import of L23a was clearly detectable. In conclusion, these data in combination with our previous results (9) suggest that there is only one functional import receptor for histone H1 in eukaryotic cells, namely the Imp␤-Imp7 heterodimer.…”
Section: Resultssupporting
confidence: 86%
“…We found that two ␤-family import receptors, namely Imp␤ and Imp7, play a critical role in the import of H1 histones (9). Each of the two import receptors binds the histone weakly when tested individually, but the binding is strong for the Imp␤-Imp7 heterodimer.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…NL1 is strongly homologous to the SV40 NLS but shares little apparent similarity to either histone H1(o) or the BIB domain, previously identified as substrates for importin 7 (Jakel and Gorlich, 1998;Jakel et al, 1999). We tested whether the residues required for import by importin ␣ were also required for the import of GR 407-525 by importin 7.…”
Section: Reconstitution Of Gr Nuclear Import In Vitromentioning
confidence: 99%